HOMOJEN VE HETEROJEN DEMİR KATALİZÖR İLE AKTİFLEŞTİRİLMİŞ PERSÜLFAT İLE SULU ÇÖZELTİLERDEN REACTİVE YELLOW 37 BOYAR MADDE GİDERİMİNİN İNCELENMESİ - KAYA, SÜMEYRA (Fırat Üniveristesi, 2022)
Bu çalışmada, homojen ve heterojen demir katalizörle aktifleştirilen persülfat (PS) ile sulu çözeltiden Reactive Yellow 37 (RY37) giderimi araştırılmıştır. PS'nin aktifleştirmesinde Fe+2 homojen katalizör ve nano sıfır değerlikli demir (nZVI) heterojen katalizör olarak kullanılmıştır. nZVI partikülleri laboratuvar şartlarında borhidrüre dayalı sıvı fazlı indirgeme metodu kullanılarak sentezlenmiştir. Çalışmada, Fe+2/PS ve nZVI/PS ile RY37 giderimi üzerinde çözelti pH'ı, katalizör konsantrasyonu, PS konsantrasyonu, başlangıç boyar madde konsantrasyonu ve sıcaklığın etkisi incelenmiştir. Ayrıca klorür, sülfat ve karbonat anyonlarının etkisi de çalışılmıştır. Çalışmada, Fe+2/PS ve nZVI/PS ile RY37 giderimi geniş bir pH aralığında etkili bir şekilde sağlanmıştır. Belli bir konsantrasyona kadar artan Fe+2 ile giderim artarken daha yüksek Fe+2 konsantrasyonlarında azalmıştır. Artan sıcaklıkla RY37 giderimi artmıştır. Her iki sistemde başlangıç boyar madde konsantrasyonu artışı ile RY37 giderimi düşmüştür. Çalışmanın sonuçları Fe+2/PS ve nZVI/PS proseslerinin RY37 giderimi için iyi bir performans sağladığını göstermiştir. Fe+2/PS ile nZVI/PS sistemleri karşılaştırıldığından nZVI/PS'nin RY37 boyar maddesini giderim performansı daha yüksek bulunmuştur. Klorür, sülfat ve karbonat iyonlarının varlığı giderim verimini olumsuz yönde etkilemiştir. Fe+2/PS ve nZVI/PS ile RY37'nin gideriminde baskın radikal tür sülfat radikali olmuştur. Elde edilen sonuçlar, Fe+2/PS ve nZVI/PS'nin sulu ortamlarda azo boyaların giderimi için büyük bir potansiyele sahip olduğunu göstermektedir.

In this study, the removal of Reactive Yellow 37 (RY37) from aqueous solution with persulfate (PS) activated with homogeneous and heterogeneous iron catalyst was investigated. Fe2+ and nano-zerovalent iron (nZVI) were used as homogeneous and heterogeneous catalyst, respectively for activation of PS. nZVI particles were synthesized using the borohydride-based liquid phase reduction method under laboratory conditions. In the study, the effects of solution pH, catalyst concentration, PS concentration, initial dyestuff concentration and temperature on RY37 removal with Fe2+/PS and nZVI/PS were examined. In addition, the effects of chloride sulfate and carbonate anions were also studied. In the study, RY37 removal with Fe2+/PS and nZVI/PS was effectively achieved over a wide pH range. While the removal increased with increasing Fe2+ up to a certain concentration, it decreased at higher concentrations of Fe2+. Temperature plays an important role in the decomposition of activated persulfate and pollutants. RY37 removal increased with increasing temperature. In both systems, RY37 removal decreased with the increase in the initial dye concentration. The results of the study showed that the Fe2+/PS and nZVI/PS processes provided good performance for RY37 removal. When Fe2+/PS system was compared with the nZVI/PS system, the RY37 dye removal performance of nZVI/PS was found to be higher. The presence of chloride, sulfate and carbonate ions negatively affected the removal efficiency. The dominant radical for the removal of RY37 by Fe+2/PS ve nZVI/PS was sulfate radical. The results obtained indicate that Fe2+/PS and nZVI/PS have great potential for the removal of azo dyes in aqueous media.
Investigation of reactive yellow 37 dye removal from aqueous solutions by persulfate activated with homogeneous and heterogeneous iron catalyst
Keywords: Çevre Mühendisliği